Modified Atmosphere Packaging (MAP) of Brown and Polished Rice - Hawa, La Choviya; Lastriyanto, Anang; Bangun, Subiantoro (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
Rice is the staple food of about 90% Indonesian people that contributed to 50% of carbohydrate requirement. The objectives of this research were to determine the weight loss, moisture content, density, texture, carbohydrate, colour and flavor of brown rice, polished rice I, and polished rice II packaged by modified atmosphere packaging (MAP). Â Experimental-descriptive method with 2 factors was used in this research. First factor was types of rice (brown rice, polished rice I, and polished rice II) and second factor was gas composition (99.56% CO2, 100% N2; and normal atmosphere 78% N2, 20.8% O2, 0.03% CO2, and 1.17% other gasses). The packaging material was polyethylene 0.08 mm in thickness. Each treatment was replicated three times. Â The results showed that storage with N2 can reduced weight loss, moisture content, and density. On the other hand, texture, carbohydrate, color and flavor of brown rice, polished rice I, and polished rice II were relatively stable. Â Storage with CO2 keep the low moisture content of rice. MAP of all types of rice was better tan normal atmosphere storage.Keywords: brown rice, polished rice, CO2, N2, modified atmosphere packaging